Dietary Guanidine Acetic Acid Improves Ruminal Antioxidant Capacity and Alters Rumen Fermentation and Microflora in Rapid-Growing Lambs - Wenjuan Li; Zhaoyang Cui; Yaowen Jiang; Ailiyasi Aisikaer; Qichao Wu; Fang Zhang; Weikang Wang; Yukun Bo; Hongjian Yang (MDPI AG, 2023)
Guanidine acetic acid (GAA) has been reported to improve growth performance, nutrient utilization, and meat quality in livestock. This study aimed to investigate whether coated GAA (CGAA) in comparison with uncoated GAA (UGAA) could have different effects on rumen fermentation, antioxidant capacity, and microflora composition in the rumen. Seventy-two lambs were randomly arranged in a 2 × 3 factorial experiment design with two diets of different forage type (OH: oaten hay; OHWS: oaten hay plus wheat silage) and three GAA treatments within each diet (control, diet without GAA addition; UGAA, uncoated GAA; CGAA, coated GAA). The whole feeding trial lasted for 120 days. The lambs in the OH group presented lower total volatile fatty acid (VFA), alpha diversity, Firmicutes, NK4A214_group, and Lachnospiraceae_NK3A20_group than those on the OHWS diet in the last 60 days of the feeding stage (p < 0.05). Regardless of what GAA form was added, dietary GAA supplementation increased the total VFA, microbial crude protein (MCP), adenosine triphosphate (ATP), and antioxidant capacity in rumen during lamb feedlotting (p < 0.05). However, molar propionate proportion, acetate:propionate ratio (A:P), and relative Succiniclasticum abundance decreased with GAA addition in the first 60 days of the growing stage, while the molar butyrate proportion and NK4A214_group (p < 0.05) in response to GAA addition increased in the last 60 days of feeding. These findings indicated that dietary GAA enhanced antioxidant capacity and fermentation characteristics in the rumen, but the addition of uncoated GAA in diets might cause some dysbacteriosis of the rumen microbiota.